Phylogenetic inferences based on distinct molecular markers reveals a novel Babesia (Babesia pantanalensis nov. sp.) and a Hepatozoon americanum-related genotype in crab-eating foxes (Cerdocyon thous) - Calchi, Ana Cláudia [UNESP]; Braga, Laíza de Queiroz Viana; Bassini-Silva, Ricardo [UNESP]; Castro-Santiago, Ana Carolina; Herrera, Heitor Miraglia; Soares, João Fábio; Barros-Battesti, Darci Moraes [UNESP]; Machado, Rosangela Zacarias [UNESP]; Rocha, Fabiana Lopes; André, Marcos Rogério [UNESP] (Elsevier, 2024)
Piroplasmids and Hepatozoon spp. Are apicomplexan protozoa that may cause disease in several canid species. The present study aimed to expand the knowledge on the diversity of piroplasmids and Hepatozoon in crab-eating foxes (Cerdocyon thous; n = 12) sampled in the Pantanal of Mato Grosso do Sul State, central-western Brazil. PCR assays based on the 18S rRNA were used as screening. Three (25%) and 11 (91.7%) were positive for piroplasmids and Hepatozoon spp., respectively. Co-infection was found in three C. thous. Phylogenetic analyses based on the near-complete 18S rRNA, cox-1 and hsp70 genes evidenced the occurrence of a novel of Babesia spp. (namely Babesia pantanalensis nov. sp.) closely related to Rangelia vitalii and Babesia sp. ‘Coco’. This finding was supported by the genetic divergence analysis which showed (i) high divergence, ranging from 4.17 to 5.62% for 18 S rRNA, 6.16% for hps70 and 4.91–9.25% for cox-1 and (ii) the genotype network (which displayed sequences separated from the previously described Piroplasmida species by median vectors and several mutational events). Also, phylogenetic analysis based on the 18S rRNA gene of Hepatozoon spp. positioned the sequences obtained herein in a clade phylogenetically related to Hepatozoon sp. ‘Curupira 2’, Hepatozoon sp. detected in domestic and wild canids from Uruguay and Hepatozoon americanum. The present study described Babesia pantanalensis nov sp. and Hepatozoon closely related to H. americanum in crab-eating foxes from Brazil. Moreover, the coinfection by piroplasmids and Hepatozoon sp. for the first time in crab-eating foxes strongly suggesting that this wild canid species potentially acts as a bio-accumulate of hemoprotozoan in wild environment.
Keywords: Apicomplexan protozoa; Babesia; Crab-eating foxes; Hepatozoon; Molecular diagnosis; Phylogeny